Neurological and Psychiatric Disorders in Patients with Rheumatic Heart Disease: Unveiling what is Beyond Cardiac Manifestations - Luiz Paulo Bastos Vasconcelos; Marcelle Cristina da Silva Bastos Vascon; Francisco Biagio Murta E. Di Flora; Flávio Augusto Paes de Oliveira; Pedro Drummond Lima; Lucas Campos Barbosa E. Silva; Breno Camargos Mucelli- Spolaor; José Luiz Padilha da Silva; William Antônio de Magalhães Esteves; Maria Carmo P. Nunes; Antônio Lúcio Teixeira (Ubiquity Press, 2022)
Background: Rheumatic heart disease (RHD) is the most serious manifestation of rheumatic fever, which may also affect the brain. The current study assessed the prevalence of neuropsychiatric manifestations in patients with RHD, including clinical features associated with basal ganglia motor dysfunction (BGMD). Methods: We conducted neurologic and psychiatric assessments in consecutive patients with RHD referred to a tertiary center for heart valve diseases. Echocardiography was performed to assess the pattern of valvular involvement and RHD severity. Validated questionnaires for the evaluation of cognition, depression, anxiety, and obsessive-compulsive symptoms (OCS) were applied. BGMD was clinically defined by the presence of hyperkinetic movement disorders. Results: Fifty patients with age of 43.2 ± 10.8 years, 84% female, were included. Mitral valve was affected in 47 patients (94%), and 21 of them (42%) also had aortic valve involvement. Chorea (22%), chronic tics (18%), OCS (48%), major depression (34%), generalized anxiety disorder (54%), cognitive complaints (66%), migraine (52%) and seizures (18%) were frequently reported. The factors associated with BGMD were age (p = 0.018), major depression (p = 0.013), and Yale-Brown Obsessive Compulsive (Y-BOCS) score (p = 0.011). The severity of heart disease was not associated with BGMD. Conclusions: Neuropsychiatric manifestations are frequent in RHD patients, which may persist up to three decades after acute rheumatic fever. Age, major depression and severity of OCS were independently associated with BGMD. These manifestations deserve a close attention of clinicians and researchers dealing with adult patients with RHD.